Genomic and phenotypic changes associated with alterations of migratory behaviour in a songbird. Issue 2 (10th November 2022) - Zhang, Dezhi; She, Huishang; Rheindt, Frank E.; Wu, Lei; Wang, Huan; Zhang, Kai; Cheng, Yalin; Song, Gang; Jia, Chenxi; Qu, Yanhua; Olsson, Urban; Alström, Per; et al.
Abstract: The seasonal migration of birds is a fascinating natural wonder. Avian migratory behaviour changes are common and are probably a polygenic process as avian migration is governed by multiple correlated components with a variable genetic basis. However, the genetic and phenotypic changes involving migration changes are poorly studied. Using one annotated near‐chromosomal level de novo genome assembly, 50 resequenced genomes, hundreds of morphometric data and species distribution information, we investigated population structure and genomic and phenotypic differences associated with differences in migratory behaviour in a songbird species, Yellow‐throated Bunting Emberiza elegans (Aves: Emberizidae). Population genomic analyses reveal extensive gene flow between the southern resident and the northern migratory populations of this species. The hand‐wing index is significantly lower in the resident populations than in the migratory populations, indicating reduced flight efficiency of the resident populations. Here, we discuss the possibility that nonmigratory populations may have originated from migratory populations though migration loss. We further infer that the alterations of genes related to energy metabolism, nervous system and circadian rhythm may have played major roles in regulating migration change. Our study sheds light on phenotypic and polygenic changes involving migration change.